Drying kinetics of Pisum sativum L. (Green peas) variety Usui - Córdova, Javier S. (2013)
The present study aimed to determine the drying kinetics parameters in Pisum sativum L., such as speed and drying time, equilibrium moisture and critical moisture; wich are very important for efficient drying and quality. Moreover, was studied removal of water present in the food, for which was used a tray dryer with hot air at 50 °C, determining moisture content of the food at different times of exposure to hot air, until achieving constant weight of food. The results obtained were: drying time and speed of Pisum sativum L. (peas green), 594,36 minutes and 0,00108 gH2O/m2.min, respectively; equilibrium moisture, 0,071 gH2O/g dry solids, and critical moisture, 0,501 gH2O/g dry solids. The values obtained were analyzed using the drying curve and determined by the analytical method of food drying theory.